PENGARUH BEBERAPA JENIS URINE TERNAK TERHADAP PERTUMBUHAN DAN PRODUKSI RUMPUT RAJA (Pennisetum Purpuphoides) DI KECAMATAN BABUL MAZMUR KABUPATEN ACEH TENGGARA - Saputra, Adi; Meriksa Sembiring (Bajang Institute, 2025)
This study aims to determine the effect of several types of livestock urine on the growth and production of king grass (Pennisetum purpureophoides). This research design uses a non-factorial Randomized Group Design (RAK) consisting of 4 treatments and 6 replicates. P0 : King grass (using soil media), P1: King grass (using soil media + goat urine liquid fertilizer), P2: King grass (using soil media + cow urine liquid fertilizer) and P3: King grass (using soil media + buffalo urine liquid fertilizer). The response of king grass to several types of livestock urine in soil media by applying to king grass plants in 5% livestock urine which is sprinkled around the grass for each treatment using 100 ml of each king grass stem. The application of POC was carried out the first fertilization after 2 weeks after planting and was carried out 3 times with an interval of 2 weeks until harvest. The parameters observed were height growth, stem diameter, number of tillers and fresh and dry forage production. Observations for grass height at 2, 4, 6 and 8 mst, while for the number of tillers and stem diameter were carried out before harvest (40 hst) and fresh forage production was carried out at harvest by weighing after cutting for each different plot then each fresh weight treatment plot was dried to get dry weight production. Data from the results of the study were analyzed statistically, if in the test there were significantly different results (p <0.05) then it would be continued with testing using DMRT. The results showed that the use of POC from the urine of several livestock showed significantly different (p<0.05) on the growth of plant height, stem diameter, number of tillers and fresh and dry forage production. The best use of liquid organic fertilizer from this study was obtained in treatment P1 (soil media + goat urine liquid fertilizer).